Zn(ii) phthalocyanines tetra substituted by aryl and alkyl azides: design, synthesis and optical detection of H2S - Albakour, Mohamad; Ongun, Merve Zeyrek; Topal, Sevinc Zehra; Gürek, Ayşe Gül (Royal Soc Chemistry, 2020)
Two novel Zn(ii)-phthalocyanines having: (i) aryl azide (3) and (ii) alkyl azide (7) functional groups at the peripheral positions have been designed/synthesized for hydrogen sulfide (H2S) sensing purposes, and their photocharacteristic properties were investigated in DMSO and THF. In these designs, we aimed to understand the effect of the groups (aryl or alkyl) bonding azide groups on the H2S sensitivity. The reduction of four azide groups on compound 3 changed the characteristics of the zinc phthalocyanine core, and it led to the appearance of a new band with a 32 nm bathochromic spectral shift in the absorption band and 88% emission quenching of 3 compared to the original intensity. The detection limits were determined to be 0.14 and 0.68 mu M in DMSO and THF, respectively. Besides, compound 7 did not show any response towards H2S.
Keywords: Ratiometric Fluorescent-Probe; One-Pot Synthesis; Hydrogen-Sulfide; Photochemical Properties; Selective Detection; Cell; Reduction; Strategy; Sensor; Acids